If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 3 = -3 + x Reorder the terms: 3 + 7x = -3 + x Solving 3 + 7x = -3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 7x + -1x = -3 + x + -1x Combine like terms: 7x + -1x = 6x 3 + 6x = -3 + x + -1x Combine like terms: x + -1x = 0 3 + 6x = -3 + 0 3 + 6x = -3 Add '-3' to each side of the equation. 3 + -3 + 6x = -3 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = -3 + -3 6x = -3 + -3 Combine like terms: -3 + -3 = -6 6x = -6 Divide each side by '6'. x = -1 Simplifying x = -1
| 2x-3y+42=1 | | 2a^2-15a+25=0 | | 0=-7t^2+10t+5 | | -(7b+3)= | | x+4+2=3 | | g[f(5)]=2x-1[4x(5)] | | 8e^4x-28=125 | | 8e^4x-28=128 | | 178.35=2.69x+15.94 | | C=2.69+15.94 | | 38=3(x+6)-8x | | 14x-114=-94 | | 7+5(x-2)=10-5(x-7) | | 2v+3(v-4)=38 | | 12=-3u+6(u+4) | | -36=-2y+4(y-6) | | 2(b+4)=20 | | h(t)=-16t^2+128t+32 | | 2(t-7)=20 | | 6.1x-2.7=3.4 | | 4a^2-26a-40=0 | | 43.61+.2x=100 | | (n!)^3/(3n)! | | 43.61(.2x)=100 | | 23=4x-2 | | 43.61(.2)=100 | | .36(6)+.06x=.18(30+x) | | 4a^2-26a+40=0 | | .8(1+.5x)=-2 | | 4x+4z=2+3y | | 3x+24=8 | | X=195-y |